2013
DOI: 10.1038/srep02884
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages lift off surface-bound bacteria using a filopodium-lamellipodium hook-and-shovel mechanism

Abstract: To clear pathogens from host tissues or biomaterial surfaces, phagocytes have to break the adhesive bacteria-substrate interactions. Here we analysed the mechanobiological process that enables macrophages to lift-off and phagocytose surface-bound Escherichia coli (E. coli). In this opsonin-independent process, macrophage filopodia hold on to the E. coli fimbriae long enough to induce a local protrusion of a lamellipodium. Specific contacts between the macrophage and E. coli are formed via the glycoprotein CD48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
64
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 50 publications
5
64
0
1
Order By: Relevance
“…Studies of AMP effects on single cells within model biofilms would represent a larger step towards realistic environments [41, 42]. It should also be possible to adapt the methods outlined here to direct, time-resolved imaging of the fate of bacterial cells as they are attacked by neutrophils or macrophages [43]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies of AMP effects on single cells within model biofilms would represent a larger step towards realistic environments [41, 42]. It should also be possible to adapt the methods outlined here to direct, time-resolved imaging of the fate of bacterial cells as they are attacked by neutrophils or macrophages [43]. …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kress et al (6) reported that filopodia act as "phagocytic tentacles" and pulled IgG-coated beads in an optical trap with discrete steps, suggesting that a motor protein was involved. More recently, Möller et al (7) reported that macrophages can use filopodia to lift membrane-bound bacteria, thereby enabling a lamellipodial protrusion to engulf the target in a so-called hook-and-shovel mechanism.…”
mentioning
confidence: 99%
“…For instance, invadopodia, podosomes, and filopodia are crucial for invasion and migration of cells (1). Filopodia are thin (100 to 300 nm), tube-like, actin-rich structures that function as "antennae" or "tentacles" that cells use to probe and interact with their microenvironment (2)(3)(4). Such structures have been studied in vitro using model systems where the point-like 3D contacts with the extracellular matrix (ECM) have been mimicked by using optically trapped dielectric particles, functionalized with relevant ligands.…”
mentioning
confidence: 99%